PRESENCE OF TRYPANOSOMA SP. IN COLLARED PECCARIES (TAYASSU TAJACU) REARED IN CAPTIVITY IN THE TROPICS OF PERU - Gómez P., Luis (2010)
The objective of the present study was to determine the presence of Trypanosoma sp. in collared peccaries reared in captivity in Iquitos and Moyobamba area. Blood samples were collected from 40 animals from 3 months to 2 years of age. Samples were processed by the microcapillary or Woo technique and the blood smear. None of the samples resulted positive to Trypanosoma sp., and probably the low sensitivity of the techniques affected the results. The Monte Carlo risk analysis (@Risk) indicated that the probability to obtain an infected animal in the Moyobamba and Iquitos area was 0.02% and that 95% of the samples were within an interval of 0.006 a 0.854%.